PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN FINANCIAL RATIOS TERHADAP FINANCIAL DISTRESS PERUSAHAAN OTOMOTIF - Rivaldy Yohannes Yosis Wati; Herman Karamoy; Lintje Kalangi (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
This study aims to analyze the effect of the board of directors, board of commissioners, liquidity, leverage and profitability on financial distress in automotive companies in the 2016-2020 period. This study uses a quantitative approach with secondary data obtained from the website of Indonesia Stock Exchange. Determination of the sample using purposive sampling method and resulted 60 research samples. The data analysis used in this study is multiple linear regression analysis. This research found that board of directors, board of commissioners, liquidity, profitability and leverage have significant influence on financial distress in automotive sub-sector companies.